2013
DOI: 10.2478/afe-2013-0048
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Squeeze Parameters and Modification of AlSi7Mg Alloy

Abstract: The paper present the examination results concerning mechanical properties of castings made of AlSi7MG alloy in correlation both with the most significant squeeze casting parameters and with the modification treatment. Experiments were planned and held according to the 23 factorial design. The regression equations describing the influence of the squeeze pressure, the mould temperature, and the quantity of strontium modifier on the strength and elongation of the examined alloy were obtained. It was found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…al. [2] used two level full-factorial design of experiment to study the effect of squeeze pressure, die temperature and percentage of modifier on percent elongation and tensile strength of squeeze cast components. Further linear and non-linear regression models were successfully applied to establish the input-output relationship in different casting processes, namely cement bonding molding, [3][4], green sand molding [5][6], resin-bonded sand mold [7], sodium-bonded molding system [8], die casting [9][10][11] and evaporative casting process [12].…”
Section: Many Of the Researchers Have Successfully Applied Doe Andmentioning
confidence: 99%
“…al. [2] used two level full-factorial design of experiment to study the effect of squeeze pressure, die temperature and percentage of modifier on percent elongation and tensile strength of squeeze cast components. Further linear and non-linear regression models were successfully applied to establish the input-output relationship in different casting processes, namely cement bonding molding, [3][4], green sand molding [5][6], resin-bonded sand mold [7], sodium-bonded molding system [8], die casting [9][10][11] and evaporative casting process [12].…”
Section: Many Of the Researchers Have Successfully Applied Doe Andmentioning
confidence: 99%
“…Castings produced by this method are also characterized by a smooth surface, no surface defects and a shape very similar to the final product. The cost-effectiveness of the process is also associated with the fact of lower energy and material consumption, even up to 98% of molten metal, by eliminating the gate assembly, strain relief and feeding head [7]. Due to the lack of a running gate system and limited flow of liquid metal, even low-castability plastic alloys can be used in this method, however, it can not be too small, because it leads to casting defects such as cold laps [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…After that time the upper part of the die was lifted up and the casting was ejected by four ejector pins placed in the corners of the slab. The parameters of the squeeze casting process were determined on the basis of previous study[7,13], in which the effect of applied pressures during casting on the tensile strength and solidification of aluminum castings was analyzed. The samples for strength tests were taken in the same way as the internal sample presented in Fig.3.…”
mentioning
confidence: 99%
“…For example, Wang et al [41] reported that the high quality of the squeeze cast aluminum alloy scroll can be obtained using the semi-solid squeeze casting process under optimal parameter values. Hence, many designs of experimentbased investigations have been conducted to determine the optimal squeeze casting process parameters [31,[42][43][44] . This paper presents the outcomes of important past work conducted to examine the performance of squeeze casting technology.…”
mentioning
confidence: 99%